Audiological findings in individual with glomus tympanicum: A case report (Indian Journal of Case Reports, 2018)
Paragangliomas are also called glomus tumors, a rare, neuroendocrine neoplasm that arises from the paraganglia in the glomus cells derived from the embryo in the neural crest of the sympathetic nervous system (a branch of the autonomic nervous system). This case report is on glomus tympanicum on the right side in a 36-year-old male presented with pulsatile tinnitus and ear pain. On otoscopic examination and radiological findings, it appears as a reddish mass behind the tympanic membrane. The pre-operative and the post-operative audiological findings are profiled and discussed.